Inferring chronological age from DNA methylation patterns of human teeth. Issue 4 (15th December 2015) - Giuliani, Cristina; Cilli, Elisabetta; Bacalini, Maria Giulia; Pirazzini, Chiara; Sazzini, Marco; Gruppioni, Giorgio; Franceschi, Claudio; Garagnani, Paolo; Luiselli, Donata
ABSTRACT: Objective: Current methods to determine chronological age from modern and ancient remains rely on both morphological and molecular approaches. However, low accuracy and the lack of standardized protocols make the development of alternative methods for the estimation of individual's age even more urgent for several research fields, such as biological anthropology, biodemography, forensics, evolutionary genetics, and ancient DNA studies. Therefore, the aim of this study is to identify genomic regions whose DNA methylation level correlates with age in modern teeth. Methods: We used MALDI‐TOF mass spectrometry to analyze DNA methylation levels of specific CpGs located in the ELOVL2, FHL2, and PENK genes. We considered methylation data from cementum, dentin and pulp of 21 modern teeth (from 17 to 77 years old) to construct a mathematical model able to exploit DNA methylation values to predict age of the individuals. Results: The median difference between the real age and that estimated using DNA methylation values is 1.20 years (SD = 1.9) if DNA is recovered from both cementum and pulp of the same modern teeth, 2.25 years (SD = 2.5) if DNA is recovered from dental pulp, 2.45 years (SD = 3.3) if DNA is extracted from cementum and 7.07 years (SD = 7.0) when DNA is recovered from dentin only. Discussion: We propose for the first time the evaluation of DNA methylation at ELOVL2, FHL2, and PENK genes as a powerful tool to predict age in modern teeth for anthropological applications. Future studies are needed to apply this method also to historical and relatively ancient human teeth. Am J Phys Anthropol 159:585–595, 2016. © 2015 Wiley Periodicals, Inc.